An Ethiopian FABLE: Making integrated water–energy–food–ecosystems futures visible - CGIAR Initiative on NEXUS Gains (CGIAR System Organization, 2024)
Actors depending on and affecting outcomes in one part of the water–energy–food–ecosystems (WEFE) nexus implicitly also make decisions that affect other sectors in intricate ways that aren’t easy to foresee or understand. A tool like the FABLE calculator can help change that. NEXUS Gains and the Ethiopian FABLE team have developed a simplified scenario analysis tool that supports government and other actors in understanding the consequences of choosing alternative food and land-use pathways. A dashboard, developed with support from NEXUS Gains, converts the data from the model into eye-opening visual demonstrations of on-the-ground-impacts of different policy decisions.